Forming Information Literacy of a Foreign Language Teacher in the Conditions of Digital Era - S. A. Deryabina; T. A. Dyakova (Высшее образование в России, 2019)
The modern educational space is characterized by its gradual digitalization and inclusion of electronic educational platforms not only in distance education, but also in online interaction between a teacher and a full-time student. Moreover, students devote more time to learning on their own. In such conditions, teachers spend more time on developing and providing electronic teaching materials, which means changes in the requirements for the teacher’s information literacy. It is getting more important to look for the most effective methods of teaching, the ways of providing information and material. Moreover, it is necessary to create a natural learning environment in the conditions of digitalization, which provides for productive activities, the development of a student’s personality, and cognitive processes. Methodologists try to obtain traditional results from online interaction. Modern universities often use electronic educational platforms where teachers can provide their courses supplementing the classroom work. The success of such teaching combined with computer technologies will largely depend on the teacher’s ability and willingness to use the Internet. This article is devoted to a foreign language teacher’s professiogram in the conditions of digitalization of the educational process and a wide use of electronic educational platforms. We will focus on the teacher’s professional competence, which allows to organize online interaction between teachers and students and to promote e-learning.